Socio-economic disparities in the utilization of improved sanitation facilities among Indian households - Pradeep Kumar; Nihal Hasan; Rahul Rajak (Scientific Reports)
Abstract Despite the significant improvement in sanitation coverage , utilization of improved sanitation still does not reach the optimal level across all socioeconomic groups in India. Therefore, achieving improved sanitation facilities and reducing all forms of inequality United Nations Sustainable Development Goal [SDG 6.2] by 2030 is a big challenge to the most populous country in the world. Given this backdrop, this study examines the socioeconomic status-related inequality in the utilization of improved sanitation facilities among Indian Households. The study utilized fifth round of National Family Health Survey (NFHS); a national representative cross-sectional survey of India conducted in 2019–2021. Logistic regression was applied to estimate the effect of various predictors on utilization of improved sanitation facilities. We also used decomposition analyse to identify the factors responsible for utilization of improved sanitation. The results indicate that 69% of Indian households utilized improved sanitation facilities. The study highlights that young and unmarried household heads, lower education, poor household wealth status, living in rural areas, and marginalized social groups had lower access to improved sanitation facilities. The multivariate regression analysis suggested that households belonging to richer [AOR: 14.0; 95%, CI: 13.6–14.3] and richest [AOR: 46.7; 95%, CI: 45.0–48.5] wealth quintiles have 14 and 47-times higher odds of having sanitation facility than households which belong to poorest quintile respectively. The decomposition analysis suggested that 11 to 18% of inequality was explained by the geographical region and social group of household heads. The concentration curve of utilization of improved sanitation was more concentrated in Central and Eastern part of Indian households (Concentration Index: 0.51 and 0.47), which has reduced to 0.17 and 0.22 during NFHS-4 to NFHS-5. We also found that 68 districts out of 707 districts in India had less than 50% utilization of improved sanitation facilities. The study concludes that households with a better socioeconomic status were more able to access improved sanitation. Thus, inclusive strategies are needed to reduce socioeconomic inequality at the micro level and strengthen ongoing policies.